THE EFFECT OF EDUCATIONAL TECHNOLOGY TOOLS ON PROMOTING STUDENT'S COLLABORATIVE WRITING - Onyia, Mary (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Collaborative writing in the educational setting has received wide research attention in recent decades. However, little is known about the impact of educational technology software in enhancing students' collaborative writing in the Nigerian context. The present paper examined wiki as an ed-tech tool that could promote students' collaborative writing in Enugu state, Nigeria. The study included ninety-six (n=96) undergraduates from a public higher education institution in Enugu state. The study adopted a quasi-experimental pre-test and post-test method. The results showed that wiki considerably improved students' writing skills. It was also discovered that the web application offers elements that promote collaborative learning among users. The result has implications for the development of effective writing in education.